The Influence of Service Quality toward Customer Satisfaction and Customer Loyalty of Bank Mandiri Syariah Ltd. Malang - Mareza Rifky Rahmadona (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
The research aims to analyse the Influence of Service Quality toward Customer Satisfaction and Customer Loyalty of Bank Mandiri Syariah Malang. The research method is quantitative with explanatory research which explains the causal relation between the variables through hypothesis testing. The data collection technique used questionnaires and literature research. This research used 110 samples of Bank Mandiri Syariah customers in Malang Those samples were taken using a purposive sampling technique. Test instrument that was used for testing the research instrument are validity test and reliability test. The analytical methods that were used are path model analysis using SPSS 20. The result in this research shows that there is a significant influence between the qualities of service to customer satisfaction, the customer satisfaction to customer loyalty shows significant result, which service quality has significant influence toward customer loyalty, neither indirectly to customer loyalty through customer satisfaction. And also Bank Syariah Mandiri Ltd. must remain active in research and development of quality services in the effort to give a consistent good impression.Key Words: Service Quality, Customer Satisfaction, Customer Loyalty, Bank Mandiri Syariah Malang